Ten years of HPV vaccination in the Netherlands: current evidence and future challenges in HPV-related disease prevention - V. Qendri; T. M. Schurink-Van ’t Klooster; J. A. Bogaards; J. Berkhof (Expert Review of Vaccines, 2018)
Introduction: Girls-only vaccination against human papillomavirus (HPV) type 16 and 18 was implemented in the Netherlands in 2009. Despite the evidence of the efficacy against precancerous lesions, cross-protection induced by the vaccine and a greater potential for cancer prevention than cervical cancer only, vaccine coverage in the girls-only program has remained below target levels. Areas covered: In this paper, we review the literature from the Netherlands on the effectiveness and cost-effectiveness of HPV vaccination since vaccine introduction, give an account of the coverage, safety and effectiveness of HPV vaccination as has been reported in the Dutch surveillance program and discuss challenges of the current HPV vaccination program. Expert commentary: Girls-only HPV vaccination may confer a substantial health gain in HPV-related disease prevention. However, vaccine coverage declined remarkably recently possibly related to safety concerns, limiting the benefits from girls’ vaccination and increasing the potential additional benefit of sex-neutral HPV vaccination. Considering the emergence of novel vaccination and screening options and the change from cytology- to HPV-based screening in 2017, further research is required to inform decisions on the optimization of an integrated vaccination and screening program.